PELATIHAN PENGOLAHAN LIMBAH RUMAH TANGGA MENJADI PUPUK ORGANIK DI DESA JUBUNG KABUPATEN JEMBER - Desthariani, Arfiane; Harsanti, Restiani Sih; Fariroh, Indri; Usmadi; Sundahri; Slameto; Aritonang, Firman (PAPUMA: Journal of Community Services, 2026)
In the daily life of Indonesian people, it is inseparable from the problem of waste produced by human life which can cause environmental pollution. The average population in Indonesia has not properly processed the waste produced, especially in Jubung Village, Sukorambi District, Jember Regency. Usually, residents dispose of waste by burning it or not processing it. This causes serious problems such as unpleasant and disturbing odors, besides it will trigger the growth of microorganisms that cause disease. One effort to deal with this problem is to conduct training and processing of household waste by converting household waste or waste into organic fertilizer that can be used as a source of nutrition for plants. Training in making organic fertilizers from agricultural waste in the form of kitchen waste (vegetables) was chosen in this activity because most of the population in Jubung Village works as farmers. The activity was carried out in 3 stages, namely socialization, counseling, and practice of making organic fertilizers. The results obtained from this community service activity were that farmers can directly practice how to process household waste by converting it into useful organic fertilizers. This training was very useful for increasing knowledge and skills as well as creativity in processing household waste into organic fertilizers.